PENGGUNAAN STRATEGI BELAJAR HIRAGANA PADA MAHASISWA ANGKATAN 2022 PROGRAM STUDI PENDIDIKAN BAHASA JEPANG FKIP DI UNIVERSITAS RIAU - Sakinah, Nur; Basri, Merri Silvia; Yohani, Adisthi Martha (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: This study is a quantitative descriptive study which aims to determine the use of independent learning strategies by class of 2022 students when learning hiragana letters. The population and sample in this study are all students from the class of 2022, totaling 38 students. The instrument used in this study was a questionnaire consisting of 26 statements. Based on the result of the questionnaire analysis, it is known that Barbara Bourke’s use of learning strategies includes 14 strategies, namely association strategies, story strategies, frequency strategies, experience strategies, visual strategies, self-monitoring strategies, compensation strategies, sequence strategies, physical/emotional response strategies, sound strategies, writing sequence strategies, learning planning strategies, learning evaluation strategies, and collaborating strategies with other people.Key Words: Learning Strategies, Hiragana, Japanese